2003
DOI: 10.1364/ol.28.002225
|View full text |Cite
|
Sign up to set email alerts
|

Scalar modulation instability in the normal dispersion regime by use of a photonic crystal fiber

Abstract: Modulation instability at high frequencies has been demonstrated in the normal dispersion regime by use of a photonic crystal fiber. This fiber-optic parametric generator provides efficient conversion of red pump light into blue and near-infrared light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
131
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(143 citation statements)
references
References 9 publications
8
131
0
4
Order By: Relevance
“…Supercontinuum generation experiments primarily use wavelengths longer that the ZDW, pumping in the anamalous dispersion region. Recently pumping slightly blue shifted into the normal dispersion region has been shown to generate widely separated, phase matched, parametric amplification peaks [23]. It is this discovery that has stimulated our recent exploration of PCF optical nonlinearities at the single photon level [21,24,25,26].…”
mentioning
confidence: 99%
“…Supercontinuum generation experiments primarily use wavelengths longer that the ZDW, pumping in the anamalous dispersion region. Recently pumping slightly blue shifted into the normal dispersion region has been shown to generate widely separated, phase matched, parametric amplification peaks [23]. It is this discovery that has stimulated our recent exploration of PCF optical nonlinearities at the single photon level [21,24,25,26].…”
mentioning
confidence: 99%
“…The material dispersion of silica is intrinsic; therefore, only the waveguide dispersion is useful in tailoring the fiber dispersion. Sufficiently large waveguide dispersion can be achieved by confining the fiber mode very tightly, as in for example photonic crystal fibers (PCFs) [1]. However, large mode area (LMA) fiber designs are necessary for power scaling, and material dispersion often becomes the dominant contribution for larger core sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In optical fibers, MI results from the interplay between chromatic dispersion and the intensity-dependent refractive index. In the usual scalar-free propagation, the phase matching of the underlying four-wave mixing process requires anomalous dispersion.3 However, phase matching can also be achieved in normal dispersion region by considering extra degrees of freedom such as polarization in birefringent 5 and isotropic 6 fibers, bimodal fibers, 7 working around the zero-dispersion wavelength (ZDW), [8][9][10] or inserting the fiber within a cavity.11 Scalar MI in free propagation through a single-mode optical fiber is usually described by the nonlinear Schrödinger equation (NLSE), in which the propagation constant is expanded in a Taylor series in the frequency domain. It has been shown that only even-order terms contribute to the MI gain and that development up to the fourth order must be considered when the pump wavelength is close to the ZDW.…”
mentioning
confidence: 99%
“…[8][9][10] To our knowledge, intracavity MI leading to a single frequency has been studied only in relatively strong dispersion regions where models including up to the second-order dispersion term are relevant to describe its dynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation